METHODOLOGICAL AND ORGANIZATIONAL - LEGAL FOUNDATIONS OF DIGITIZATION OF PUBLIC CONTROL - Usmanov, Otabek (Educational Research in Universal Sciences, 2023)
this article gives an interpretation of public control, stages of its historical development, factors of improving public control under the influence of theoretical social factors, stages and other components of the term public control. Specific stages in the development of public control and its main systems, organizational and legal mechanisms, best practices of public control in scientific research and research results, problems and their solutions in the field of public control, scientific conclusions on the introduction of new and modern forms of public control and further improvement their legal bases. And also such questions as “Methods of further strengthening and improvement of public control”, “Mechanisms of public control”, “Methodological concepts of public control and examples of research by scientists in international experience”, “National experience of public control mechanisms”, “General public control”, “Prospects for the development of public control” were analyzed. From the proposals and recommendations put forward in this scientific article, lessons can be learned for understanding the initial concepts of public control, with the aim of its theoretically complete analytical study. Also, it can be used to study the scientific and theoretical aspects of public control, the development of national legislation on public control, ensuring the rule of law by further strengthening the practice of public control.